Entrepreneurship in a Gender Perspective in Indonesia Sub-Urban - Yayat Sujatna; Siti Maryama (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: The purpose of this study is to analyze the interests and differences in entrepreneurship interests based on a gender perspective. Design/methodology/approach: The research method was designed with a descriptive approach and different tests using primary data. Primary data were collected through distributing questionnaires to 100 respondents using purposive sampling technique with a linkert scale. Findings: The results showed that the level of Advertisy Quotien, Self Efficacy, Need for Achievement, and Entrepreneurial Intention between men and women was quite high. In this study also found no differences in Advertisy Quotien, Self Efficacy, Need for Achievement, and Entrepreneurial Intention between men and women. Research limitations/implications: The research sample was taken from the city of South Tangerang by random technique Practical implications: In a gender view or study, entrepreneurship has no influence or difference between men and women. that is, all people whether male or female have the same level of ability and ability in entrepreneurship. Originality/value: Paper type: This paper can be categorized as case study paper